Challenges regarding the internationalisation of universities from Scotland, within the Brexit landscape - Violeta Mihaela Dincă; Richard Ingram; Christopher Herriot; Corina Pelău (Amfiteatru Economic Journal, 2019)
The international labour market of 2018 can be characterized as very competition driven and for anyone who aspires at a professional evolution, international knowledge and skills have become required and indispensable for success. Universities emerged as the essential centre of the internationalisation strategies of governments in many countries of the world because they represent key providers of the afore-mentioned knowledge and skills. The process of internationalisation of higher education clearly has certain advantages for the students and academic staff of the undergraduate and graduate schools, but also for the national economy, and the international community. Yet in each country there is a different degree of importance given to each of these multiple benefits. The objectives of this research had two principal focuses: 1) to identify the benefits of the internationalisation process of higher education in Scotland and 2) to investigate which measures are most effective for accomplishing these benefits given the background of an uncertain climate influenced by Brexit. A questionnaire was used to obtain the views of representatives of all 19 Scottish universities of Scotland, as to the current situation in their country. The results reveal the range of approaches taken by these universities when advocating the process of establishing an international basis to higher education, but, also in their respective internationalisation strategies. Securing the respondents was possible within the Erasmus+ project developed in 2017, titled 'University Study Visit: Youth and Community Work in Scotland'. During this project academics and experts were consulted regarding their views on ways to improve the cooperation between Scottish universities and those of the European Union having as a background an economic, social and political context permeated with Brexit concerns. Their suggestions were included in the study as recommendations for strengthening the ties between the EU and Scottish universities.
Keywords: I23; F53; 330; Higher education; internationalisation process; Scotland; strategy